2019
DOI: 10.4025/actascianimsci.v42i1.46070
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine requirement for European laying quail

Abstract: The experiment was carried out to evaluate the productive performance of European quails (Coturnix coturnix) in the production phase, fed with diets containing different levels of digestible lysine. A total of 175 female quails, aged 65 days, were randomly distributed in a completely randomized design with five treatments and five replicates per treatment. The animals were housed in 25 metal cages, and each cage represented an experimental parcel, with seven birds per parcel. The birds were fed the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…Birds fed with maize germ meal had heavier eggs, a result which agrees with Severo et al (2020), who found that the weight of the European quail egg reached a maximum of 23.92 g when fed with 43% maize meal and 1.417% digestible lysine. Sultana et al (2007) found Japanese quail produced egg weighing 9.74g when fed with a 60% maize diet, while Research, Society and Development, v. 9, n. 11, e76691110370, 2020(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10370 Parizadian et al (2011 reported mean egg weights of 11.91g for Japanese quail fed a diet of 50% maize.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Birds fed with maize germ meal had heavier eggs, a result which agrees with Severo et al (2020), who found that the weight of the European quail egg reached a maximum of 23.92 g when fed with 43% maize meal and 1.417% digestible lysine. Sultana et al (2007) found Japanese quail produced egg weighing 9.74g when fed with a 60% maize diet, while Research, Society and Development, v. 9, n. 11, e76691110370, 2020(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10370 Parizadian et al (2011 reported mean egg weights of 11.91g for Japanese quail fed a diet of 50% maize.…”
Section: Discussionsupporting
confidence: 89%
“…Feed conversion was better for birds fed with maize germ meal, this probably occurred as a function of the significant increase in the content of essential unsaturated fatty acids present in the maize germ meal. Severo et al (2020) reported that European quails fed with 43% maize meal and 1.417% digestible lysine showed a feed conversion ratio of 2.98, a value much higher than that found in this research (< 2.41 to all diets). For laying hens, Brunelli et al (2010) noted that the inclusion of up to 21.2% of maize germ meal greatly improved feed conversion.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The amount of energy in the diet influences feed consumption, and can interfere with egg production and egg constituents, and consumption is also influenced by factors such as body weight, ambient temperature, photoperiod, among others (Severo et al, 2020;Santana et al, 2021). When there is an increase in the energy level of the feed, voluntary consumption decreases, reducing egg production (Silva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%